ANALYSIS OF THE INFLUENCE OF EMPLOYEE PERFORMANCE THROUGH JOB STRESS, WORKLOAD AND WORK DISCIPLINE - Susi Handayani; Muhammad Iqbal; Lila Bismala; Hafsah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The aim of this research is to determine and analyze the influence of employee performance through work stress, workload and work discipline at PT. North Sumatra Medan Bank Coordinator Branch Office either partially or simultaneously. The approach used in this research is an associative approach. The population in this study were all employees of PT. Medan North Sumatra Bank Coordinator Branch Office. The sample in this study used the Slovin formula, totaling 60 employees at PT. Medan North Sumatra Bank Coordinator Branch Office. Data collection techniques in this research used interview techniques, documentation studies, observations and questionnaires. The data analysis technique in this research uses Multiple Linear Regression Analysis Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this research used the SPSS (Statistical Package for the Social Sciences) software program version 24.00. The results of this research prove that partially and simultaneously work stress, workload, work discipline have a significant effect on the performance of PT employees. Medan North Sumatra Bank Coordinator Branch Office